Breathing pattern in highly competitive cyclists during incremental exercise - Lucia, A.; Carvajal, A.; Calderon,F. J.; Alfonso, A.; Chicharro, J. L. (European Journal of Applied Physiology, 1999)
The breathing pattern of the two groups of cyclists (professional and amateurs differed mainly in two aspects: in the professional cyclists, V˙E increased at any exercise intensity as a result of increases in both VT and fb, with no evidence of tachypnoeic shift, and tE was prolonged in this group at high exercise intensities. In contrast, neither the central drive nor the timing component of respiration seem to have been significantly altered by the training demands of professional cycling.